2016
DOI: 10.3208/jgssp.jpn-118
|View full text |Cite
|
Sign up to set email alerts
|

Liquefaction damage enhanced by interference between the body wave and surface wave induced from the inclined bedrock

Abstract: One of the important characteristic of the liquefaction damage observed at Urayasu city during the Great East Japan Earthquake is that liquefied and non-liquefied site was inhomogeneously distributed. The difference in damage levels has often been explained by the presence/absence of past ground improvement and by the difference in the dates of reclamation work. Such causes of extensive damage are, no doubt, correct. However, sufficient explanations have not been provided yet concerning the mechanism of liquef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Pender et al (2016) used V s = 400 m/s for the elastic half-space to investigate the effect of permeability on the cyclic generation and dissipation of pore pressures in saturated gravel layers in Christchurch, New Zealand. Fukutake and Jang (2013) and Nakai et al (2016) used a V s of 430 m/s and 400 m/s for liquefaction potential studies in Urayasu, Japan. Mase et al (2022) used V s = 400 m/s as elastic half-space for liquefaction analysis in Osaka, Japan.…”
Section: Priors and Likelihoods Of Site Amplificationsmentioning
confidence: 99%
“…Pender et al (2016) used V s = 400 m/s for the elastic half-space to investigate the effect of permeability on the cyclic generation and dissipation of pore pressures in saturated gravel layers in Christchurch, New Zealand. Fukutake and Jang (2013) and Nakai et al (2016) used a V s of 430 m/s and 400 m/s for liquefaction potential studies in Urayasu, Japan. Mase et al (2022) used V s = 400 m/s as elastic half-space for liquefaction analysis in Osaka, Japan.…”
Section: Priors and Likelihoods Of Site Amplificationsmentioning
confidence: 99%
“…However, the report was limited to the study of resonance in high-rise buildings and oil tank sloshing damage, and did not mention any effects on ground damage at all. Regarding these matters, the authors conducted a 2D elasto-plastic seismic response analysis considering stratum irregularities, and numerically confirmed that complex wave propagation due to stratum irregularities causes severe and nonuniform liquefaction damage (Nakai et al, 2016). Although the authors suggested that surface waves excited at the base of the irregularity near the ground surface were the important cause, validation of the numerically represented surface waves including the effect of analytical region and finite element mesh division, etc., was not sufficient because of the narrow analytical model region.…”
Section: Introductionmentioning
confidence: 97%
“…Using numerical techniques, Nakai et al [6] showed that ground deformation was strongly affected by the spatial distribution geological layer structures. However, they focused on the distribution of non-liquefiable layers or its inclination under the liquefiable layer.…”
Section: Introductionmentioning
confidence: 99%